2007
DOI: 10.1038/nprot.2007.515
|View full text |Cite
|
Sign up to set email alerts
|

Methods for detection, isolation and culture of mouse and human invariant NKT cells

Abstract: This protocol describes methods to identify, purify and culture CD1d restricted invariant natural killer T (iNKT) cells from mouse tissue or human blood samples. The methods for identification and purification of iNKT cells are based on the interaction between iNKT cell receptor and its ligand. The iNKT cell receptor is composed of the invariant V alpha 14 J alpha 18/V beta 8.2 in mice or V alpha 24 J alpha 18/V beta 11 in humans and is expressed only on iNKT cells but not on conventional T cells. The iNKT cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 31 publications
2
115
0
Order By: Relevance
“…Notably, the in vivo expansion of these cells peaked at day 3 postimmunization, compared with 7 d postimmunization for conventional αβ T cells (18). This speedy in vivo response is a signature of iNKT cells (17). These results indicate that the HSC-engineered iNKT cells are fully functional.…”
Section: Generation Of Clonal Inkt Cells Through Genetic Engineering supporting
confidence: 48%
See 1 more Smart Citation
“…Notably, the in vivo expansion of these cells peaked at day 3 postimmunization, compared with 7 d postimmunization for conventional αβ T cells (18). This speedy in vivo response is a signature of iNKT cells (17). These results indicate that the HSC-engineered iNKT cells are fully functional.…”
Section: Generation Of Clonal Inkt Cells Through Genetic Engineering supporting
confidence: 48%
“…Study of the iNKT cells from the B6-miNKT mice revealed that these iNKT cells displayed a typical phenotype of mouse iNKT cells in that they exhibited high expression of the NK1.1 marker, as well as a memory Tcell signature (CD62L lo CD44 hi ) and a CD4 + CD8 − or CD4 − CD8 − coreceptor expression pattern (Fig. 2F) (17). Almost all of these iNKT cells showed positive staining for TCR Vβ8, indicating that they expressed the transgenic clonal iNKT TCR and suggesting that they were derived from the miNKT-engineered HSCs (Fig.…”
Section: Generation Of Clonal Inkt Cells Through Genetic Engineering mentioning
confidence: 99%
“…Hepatic mononuclear cells (MNCs) were isolated as described by Watarai et al [14] . Briefly, each mouse liver was first perfused with Hank's balanced salt solution to eliminate blood until the liver become pale.…”
Section: Isolation Of Hepatic Mononuclear Cellsmentioning
confidence: 99%
“…Hepatic lymphocytes were isolated using a previously described protocol with minor modifications. 35 Briefly, mice were euthanized by intraperitoneal injection with pentobarbital sodium, and the liver was perfused with PBS via the portal vein until it became pale. The liver was then removed and gently pressed through a 200-gauge stainless steel mesh into PBS containing 2% FCS (Gibco, Carlsbad, CA, USA).…”
Section: Ethics Statementmentioning
confidence: 99%